Limited livelihoods: Gender and Class in Nineteenth-Century England - Thompson, Dorothy (Labour / Le Travail, 1993)
The article reviews the book,"Limited livelihoods: Gender and Class in Nineteenth-Century England," by Sonya O. Rose.
Keywords: BOOKS – Reviews; LABOR supply; LIMITED Livelihoods: Gender & Class in Nineteenth-Century England (Book); Nonfiction; ROSE; Sonya O.